Increased Plasma Dipeptidyl Peptidase-4 (DPP4) Activity Is an Obesity-Independent Parameter for Glycemic Deregulation in Type 2 Diabetes Patients - Sarkar, Jit; Nargis, Titli; Tantia, Om; Ghosh, Sujoy; Chakrabarti, Partha (Frontiers in Endocrinology, 2019)
Background: Increase in circulating dipeptidyl peptidase-4 (DPP4) activity and levels has been reported to associate both with hyperglycemia and obesity. Here we aim to decipher the role of enhanced plasma DPP4 activity in obese type 2 diabetes (T2DM) patients. Material & methods: Plasma DPP4 levels and activity were measured in obese and non-obese newly diagnosed T2DM patients (n=123). Visceral and subcutaneous adipose tissue DPP4 expression and activity were determined in 43 obese subjects (T2DM=21 and non-T2DM=22). 20 subjects undergoing Mini-Gastric Bypass (MGB) surgery were followed up over 4-6 weeks for plasma DPP4. Results: Plasma DPP4 levels and activity both were increased in T2DM patients compared to control group. However, DPP4 levels and not DPP4 activity were increased in obese T2DM patients compared to non-obese T2DM (62.49 ± 26.27 µg/ml vs 48.4 ± 30.98 µg/ml respectively, p= 0.028). DPP4 activity in visceral adipose tissue (VAT) from obese T2DM and obese non-T2DM groups were similar (5.05 ± 3.96 nmol/min/ml vs 5.83 ± 4.13 nmol/min/ml respectively, p= 0.548) in spite of having increased DPP4 expression in the obese T2DM group. Moreover, in obese patients, plasma DPP4 levels and activity did not show any significant change after weight reduction and glycemic control following MGB surgery. Conclusion: Enhanced plasma DPP4 activity in T2DM occurs independently of obesity. Thus adipose derived DPP4 may not be playing any significant role in glycemic deregulation in obese T2DM patients.